2005
DOI: 10.1177/0143034305060792
|View full text |Cite
|
Sign up to set email alerts
|

Bibliotherapy

Abstract: Children’s literature is a therapeutic tool for facilitating emotional growth and healing. Stories provide a catalyst for change, providing children with other perspectives and options for thoughts, feelings and behaviours. Appropriately shared stories provide opportunities for children to gain insight and learn healthier ways to face difficulties. To increase familiarity with bibliotherapy the following information is reviewed: a background of literature’s therapeutic use; the stages of involvement, identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 13 publications
(23 reference statements)
0
32
0
1
Order By: Relevance
“…Lesnik-Oberstein, 1998 20 Steadman & Palmer, 1997 1 Bettelheim, 1991 57 Ohler, 2006 22 Moyer, 2000 38 Cairney, 1984 58 Hunt, 2000 23 Banister & Ryan, 2001 39 Storr, 1986 59 Zeece PD, 2004 24 Riecken & Miller, 1990 40 Purves & Monson, 1984 60 Zipes, 1996 25 Batini & Giusti, 2008 41 Freud & Strachey, 1964 61 Boyd et al, 2011 26 Williams, 2000 42 Bernays, 1979 62 Hunt, 2006 27 Daniel, 2013 43 Heath et al, 2005 63 Winnicott, 1964 28 Brice, 2004 44 Wyatt, 2008 64 Nikolajeva, 1995 29 Brown, 2000 45 Piotrow & De Fossard, 2003 65 Zipes, 2013 30 Isbell et al, 2004 46 Albert, 2010 66 Kilpatrick et al,1994 31 Mokhtar et al, 2011 47 Reynolds et al, 2000 67 Guroian, 2002 32 Forgan, 2002 48 Lenkowsky, 1987 68 Zipes, 2002 33 Apol, 1998 49 Hoagland, 1972 69 Yenika-Agbaw, 1997 34 Zabel, 1991 50 Charon & Eric, 2017 70 Zeece, 1997 35 Ohler, 2013 51 Rudnytsky & Charon, 2008 71 Robin,...…”
Section: Pedagogic Dimension Didactic Dimension Therapeutic Dimensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lesnik-Oberstein, 1998 20 Steadman & Palmer, 1997 1 Bettelheim, 1991 57 Ohler, 2006 22 Moyer, 2000 38 Cairney, 1984 58 Hunt, 2000 23 Banister & Ryan, 2001 39 Storr, 1986 59 Zeece PD, 2004 24 Riecken & Miller, 1990 40 Purves & Monson, 1984 60 Zipes, 1996 25 Batini & Giusti, 2008 41 Freud & Strachey, 1964 61 Boyd et al, 2011 26 Williams, 2000 42 Bernays, 1979 62 Hunt, 2006 27 Daniel, 2013 43 Heath et al, 2005 63 Winnicott, 1964 28 Brice, 2004 44 Wyatt, 2008 64 Nikolajeva, 1995 29 Brown, 2000 45 Piotrow & De Fossard, 2003 65 Zipes, 2013 30 Isbell et al, 2004 46 Albert, 2010 66 Kilpatrick et al,1994 31 Mokhtar et al, 2011 47 Reynolds et al, 2000 67 Guroian, 2002 32 Forgan, 2002 48 Lenkowsky, 1987 68 Zipes, 2002 33 Apol, 1998 49 Hoagland, 1972 69 Yenika-Agbaw, 1997 34 Zabel, 1991 50 Charon & Eric, 2017 70 Zeece, 1997 35 Ohler, 2013 51 Rudnytsky & Charon, 2008 71 Robin,...…”
Section: Pedagogic Dimension Didactic Dimension Therapeutic Dimensionmentioning
confidence: 99%
“…20 Modern children's literature comprises short fairytales and fables, picture books, comics, cartoons, novels, nursery rhymes that can be potentially appreciated by most children. 21 In our search, we selected 17 studies concerning pedagogic dimension of children literature, 20,22-37 while 21 and 17 studies were chosen as addressing didactic 1,5,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] and therapeutic dimensions, 6,7,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] respectively (Table 1).…”
Section: Pedagogic Dimension Didactic Dimension Therapeutic Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…En esta misma línea, Aram y Biron (2004) estudian el papel que tienen los cuentos en niños de 3 a 5 años para la adquisición de la conciencia fonológica, el conocimiento de las letras así como adquirir unas buenas bases de conciencia ortográfica que permitan acceder a uso correcto de la lengua materna. Roberts (2008) analiza el valor pedagógico de los cuentos para trabajar el vocabulario en niños ingleses en edad preescolar, y Heath (2005), por su parte, sostiene que la LI es una herramienta terapéutica útil para facilitar el crecimiento emocional ya que es capaz de crear experiencias de aprendizaje positivas y productivas. Si bien no desde una línea puramente terapéutica, el estudio de O'Sullivan (2004) relaciona los beneficios de la LI para la educación del carácter de los niños en sus primeros años de escolarización.…”
Section: La LI Y Su Uso Didácticounclassified
“…A review of the literature on affective bibliotherapy offers mixed results (Riorden & Wilson, 1989), with better outcomes for issues of loss, adopted children, and in enhancing interpersonal relationships (Heath, Sheen, Leavy, Young, & Money, 2005). Several studies with aggressive boys indicated that affective bibliotherapy helps to reduce adjustment difficulties and aggressive behavior, compared with no treatment (Shechtman, 2003;Shechtman & Birani-Nasaraladin, 2006).…”
mentioning
confidence: 99%